2010
DOI: 10.1021/jo1004636
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Iron Catalysis in Transesterifications: Scope and Limitations

Abstract: The ester bond is one of the most common structural motifs found in nature. Apart from the condensation between an acid and an alcohol, transesterifications represent another mechanistic alternative for the preparation of this compound class. The present paper summarizes our most recent investigations in this field, using nucleophilic iron complexes as catalysts for transesterifications under neutral conditions. This new type of metal catalyst complements the existing methodologies, which rely on Lewis acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…14,15 The use of the diphenylmethyl imidate 2 allows for formation of diphenylmethyl esters without relying on toxic and energetic diazo reagents. In addition, no strong oxidizing agents or toxic metal salts are needed for this new esterification.…”
Section: Scheme 4 Deprotection Of Diphenylmethyl Ester 23 Without Racmentioning
confidence: 99%
“…14,15 The use of the diphenylmethyl imidate 2 allows for formation of diphenylmethyl esters without relying on toxic and energetic diazo reagents. In addition, no strong oxidizing agents or toxic metal salts are needed for this new esterification.…”
Section: Scheme 4 Deprotection Of Diphenylmethyl Ester 23 Without Racmentioning
confidence: 99%
“…[1] Clearly, most of the work in organometallic catalysis has been performed by applying noble metals based on palladium, rhodium, iridium, and ruthenium complexes. [6][7][8][9][10][11][12][13][14][15][16][17] To date, most of the work in this field has demonstrated that iron complexes can be used in the same way as noble metal catalysts. In this respect, homogeneous catalysis with iron complexes offers a highly attractive substitute.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we were able to show that Fe–acyl complexes derived from reaction of an ester with a low‐valent iron species, such as [Bu 4 N][Fe(CO) 3 (NO)] (abbreviated to TBAFe), are intermediates in transesterifications under neutral conditions 8. Whereas initial studies concentrated on the use of enol acetates,8a further investigations showed that p ‐chloro aryl esters are potent acyl donors allowing for the successful transesterification of a variety of structurally labile acid residues to various alcohols 8b…”
Section: Methodsmentioning
confidence: 99%